Risk factors associated with sexually transmitted infections among HIV infected men who have sex with men. - Yun Xian; Bowen Zhu; Xuan Zhang; Ping Ma; Ye Wei; Hongli Xia; Wenjie Jiang; Changqing Yang; Xiaojun Meng; Peng Peng; Yue Yang; Liying Jiang; et al. (PLoS ONE, 2017)
To investigate the factors associated with sexually transmitted infection and Human Immunodeficiency Virus (STI-HIV) co-infection among men who have sex with men (MSM). A total of 357 HIV-infected participants (84 STI-HIV co-infection and 273 HIV infections only) were recruited from Jiangsu, China. Logistic regression analyses were used to estimate the related factors associated with STI-HIV co-infection. Marginal structural models were adopted to estimate the effect of transmission drug resistance (TDR) on STI-HIV co-infection. For all participants, logistic regression analyses revealed that those who diagnosed with HIV-1 for longer duration (≥1.8 years) were significantly associated with reduced STI-HIV co-infection risk (OR = 0.55, 95%CI: 0.32-0.96, P = 0.036). In further stratification analysis by antiretroviral therapy (ART), individuals with longer duration showed consistent significant associations with STI-HIV co-infection risk (OR = 0.46, 95%CI: 0.26-0.83, P = 0.010) among MSM with ART-naïve status. In addition, significant reduced risk for STI-HIV co-infection (OR = 0.98, 95%CI: 0.96-0.99, P = 0.010) were observed in younger (under the average age of 31.03) MSM of the same group. Interestingly, we also found TDR was significantly associated with an increased risk of STI-HIV co-infection risk (OR = 3.84, 95%CI: 1.05-14.03, P = 0.042) in ART-naïve group. Our study highlights a pattern of STI-HIV co-infection among MSM in China and indicates that targeted interventions aimed at encouraging TDR monitoring in MSM with early HIV infection are warranted.